PENGARUH sGnRH + DOMPERIDON DENGAN DOSIS YANG BERBEDA TERHADAP PEMBUAHAN DAN PENETASAN TELUR IKAN SELAIS (Ompok rhadinurus Ng) - Nuraini '; Hamdan Alawi; Nurasiah '; Netti Aryani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
This study was conducted at fish breeding and hatchery laboratory ofFisheries and Marine Science Faculty, University of Riau. Mature female ofselais fish used in the study were between 45-50 g body weight and male fishwere between 44-55 g body weight. Study method used in the study wasexperimental method,while data was analised by descriftive method. Theresultsof the study show that the highest percentage of fertilized eggs found on thetreatment of D0, 3W7 (fish injected with sGnRH + Domperidon 0,3 ml/kg andlaten time of 7 hours), and the highest percentage of eggs hatch was found on thetreatment of D0,5W8 and D0,7W6. However, treatment without injection withsGnRH + domperidon was no single fish was ovulated. Water quality duringexperiment was always in good condition for living.Keywords: Ompok rhadinurus Ng, sGnRH + Domperidon, ovulation. fertilizedeggs, laten time.